The Response of the Auld Kirk in Haddington to the Disruption. Issue 1 (April 2021) - Dutton, David
Abstract : This article will provide a case study of how the Auld Kirk in Haddington responded to the Disruption of 1843. It will show that despite the diversification of the church in the burgh during the eighteenth and early nineteenth centuries, in 1843 the Church of Scotland was by far the largest denomination and that, despite two ministers and just under 500 members 'coming out', it retained its dominance during the remainder of the nineteenth century. This article will identify a number of factors which enabled the established church in Haddington to respond effectively to the Disruption, including the speed with which it reacted to the events of 1843; the reluctance of parishioners to leave the ancient parish church of St Mary's; the relative weakness of other denominations in the town; its ability to attract able and energetic ministers; and, its willingness to pursue a form of 'territorial ministry'.